Formulation Development and Validation of a Method for Direct, Underivatized Analysis of Orlistat in Orlistat-Loaded Solid Dispersion in Simulated Conditions - Sharma, Kiran Singh (Asian Journal of Pharmaceutics (AJP), 2022)
There is a high need of enhancing solubility of poorly soluble orlistat drug and its underivatized analysis in dosage forms due to high excipient interference present in the formulations. In this research, we 1st time account an easy, fast, selective, accurate, and specific UV–visible spectrophotometric technique and preparation of solid dispersion (SD) with cooperative effect of poloxamer 188 and spray-dried lactose. SDs were prepared by kneading method and in developed analytical technique, drug recognition was carried out using UV–visible spectrophotometer at λ max of 217.5 nm using methanol as solvent. The process validated for various parameters according to the present International Conference on Harmonization guidelines. The method demonstrated good recoveries for samples fortified with three different concentration ranges of low, mid, and high level covering the working range. The calibration graph was correlating in the concentration range of 1–10 μg/ml with the correlation coefficient of 0.9993. The accuracy was found to be in between 99.3 and 100.9%. The precision among six samples preparations was within limit, limit of detection and limit of quantification values are 0.07 and 0.238 μg/ml, respectively. The percentage recovery of the drug was found to be 100.2% which indicates that there was no interference of the capsule or other excipients with the method. The enhanced solubility of prepared SDs was translated to improved dissolution of the drug when compared with crystalline and amorphous form complementing the outcome of the solution state study. Dramatically high improvements in the dissolution rate of orlistat were achieved by a special supportive effect of poloxamer 188 with spray-dried lactose.